Resepsi Tafsir Al-Ṣāwy di Pesantren Musthafawiyah Purba Baru Mandailing Natal - Azizah Mardiyah (Jurnal Ulunnuha, 2023)
This discourse analyzes the reception of the Koran at the Musthafawiyah Purba Baru Islamic Boarding School in Mandailing Natal. The book Hasyiyah al-Ṣāwy 'Ala Tafsir Jalalain is one of the subjects in the class and seeks to explore the meaning of these various receptions. The aim of the research is to analyze asātiż's reception of al-Ṣāwy's interpretation and the meaning of its reception. Using phenomenological descriptive qualitative methods. Based on the reception held by asātiż in expounding the tafsir al-Ṣāwy, it was found that: First, the reception held by asātiż in expounding the tafsir al-Ṣāwy at the Musthafawiyah Islamic boarding school had a lecture method and showed that the tendency of the tafsir recitation carried out was not to be focused on textuality or classical texts alone. The reception variants are exegesis, aesthetic reception, and functional reception. Second, the study of tafsir in this Islamic boarding school found three meanings of reception, namely: objective, tafsir al-Ṣāwy as explanation. Expressive; Facilitate reading of the Qur'an, increase Arabic vocabulary, and imitate Ahmad bin Muhammad Al-Ṣāwy. Documentary, the context of maintaining the Qur'ān by memorizing and repeating material. Asātiż displays scenes in front of the class and formulates interpretive texts (al-Qur'ān) in an effort to understand the students.